A agricultura urbana em São Paulo e Belo Horizonte: Uma proposta de abordagem das relações urbano-rural no contexto metropolitano - Angele Proust; Maura Neves Coutinho (Confins)
Public policies on urban agriculture and food in the metropolises of São Paulo and Belo Horizonte are faced with a major challenge: that of considering a territory that is constantly changing with regard to the process of metropolization that is taking place. Urban agriculture, as a practice that disrupts the disjointed notions of city and countryside, is the practical extension of this theory through concrete actions. The implementation of actions to cultivate the soil is therefore a political practice that renews our view of the metropolis and encourages the emergence of new practices of resistance. We will show that urban agriculture has a political position in the city which encourages the alliance between the metropolitan scale, the municipal scale and the local scale, i.e. that of the urban garden.